2022
DOI: 10.1038/s41598-022-12393-0
|View full text |Cite
|
Sign up to set email alerts
|

The association between serum glucose to potassium ratio on admission and short-term mortality in ischemic stroke patients

Abstract: High serum glucose to potassium ratio (GPR) at admission is implicated for a poor outcome in acute brain injury, acute intracranial hemorrhage, and aneurysmal subarachnoid hemorrhage. However, the relationship between GPR and the outcome of ischemic stroke (IS) remains unknown. In all, 784 IS patients from a large emergency Norwegian cohort were included for secondary analysis. The exposure and outcome were GPR at baseline and all-cause mortality within 30 days after the first admission. Multivariable logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Our findings are consistent with a single-center retrospective cohort study that included 784 patients who arrived at an emergency in Norway between 2010 and 2015. Using the continuous model, the study found a significant positive correlation between GPR levels and 30-day mortality (OR 2.01 [95 % CI 1.12–3.61], p = 0.01) in ischemic stroke patients ( Lu et al, 2022 ). The study confirmed the results by categorizing GPR into three tertiles (GPR: Tertile 1: ≤ 1.372; Tertile 2: 1.375–1.658; Tertile 3: ≥ 1.659).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are consistent with a single-center retrospective cohort study that included 784 patients who arrived at an emergency in Norway between 2010 and 2015. Using the continuous model, the study found a significant positive correlation between GPR levels and 30-day mortality (OR 2.01 [95 % CI 1.12–3.61], p = 0.01) in ischemic stroke patients ( Lu et al, 2022 ). The study confirmed the results by categorizing GPR into three tertiles (GPR: Tertile 1: ≤ 1.372; Tertile 2: 1.375–1.658; Tertile 3: ≥ 1.659).…”
Section: Discussionmentioning
confidence: 99%
“…Following stress and brain trauma, catecholamines, cortisol, growth hormones, and cytokines are released due to the neuroendocrine response of the sympathetic nervous system ( Dungan et al, 2009 , Jayaraman et al, 2020 ). As a result, glucose levels rise, causing hyperglycemia, while potassium levels diminish, leading to hypokalemia ( Lu et al, 2022 , Thier, 1986 ). The Glucose-to-Potassium Ratio (GPR), which reflects glucose and potassium levels in the bloodstream, has emerged as a biomarker in various pathophysiological conditions sharing similarities with ischemic stroke, including aneurysmal subarachnoid hemorrhage ( Calviere et al, 2022 , Jung et al, 2021 , Matano et al, 2019 , Wang et al, 2021b ), acute intracerebral hemorrhage ( Wu et al, 2021 ), severe traumatic brain injury ( Marini and Sein, 2023 , Zhou et al, 2020 ), massive and non-massive pulmonary embolism ( Boyuk, 2022 ), and delayed neuropsychiatric syndrome after carbon monoxide poisoning ( Demirtaş et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although research often focuses on the mass of PM2.5, its chemical composition is crucial. The composition of PM2.5 is complex, and the physical structure, chemical composition, and source of its components are diverse 7 . Therefore, PM2.5's individual chemical components can have distinct, cumulative, and potentially synergistic health impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Low levels of serum albumin could aggravate the degree of brain edema and affect drug efficacy in patients after traumatic brain injury (Jungner et al, 2010). Albumin has been found to be associated with clinical outcomes in patients with traumatic brain injury (Wang et al, 2020) and ischemic stroke (Lu et al, 2022), but its predictive value of short-term clinical outcomes in patients with pDOC remains uncertain.…”
Section: Introductionmentioning
confidence: 99%